1999
DOI: 10.1046/j.1365-2389.1999.00269.x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling particle mobilization and leaching in macroporous soil

Abstract: Summary The migration of colloidal particles in the unsaturated zone may enhance leaching of sorbing contaminants to surface waters and groundwaters. This paper describes a simple model of particle leaching and translocation based on the dual‐porosity model MACRO. The model includes descriptions of processes such as ‘source‐limited’ particle detachment due to the kinetic energy of rain, replenishment of the depleted store of particles up to a maximum value determined by the amount of dispersible clay in the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
76
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 42 publications
2
76
1
Order By: Relevance
“…By strongly associating with the clay surfaces of WDC, transport of OM into deeper soil layers is also possible (Séquaris et al, 2010). Mechanical and chemical processes in soil are key factors which affect the stability of soil aggregates and thus the release and stability of mobile WDCs such as a combination of hydrodynamic parameters (intensive rain, splash erosion, infiltration water rate) and chemical dispersion conditions (the presence of organic matter, increasing pH, decreasing ionic strength and increasing sodium adsorption ratio (SAR)) (Jarvis et al, 1999;Kjaergaard et al, 2004a, b). It has been shown that shaking soil aggregates in low-ionic strength water simulates erosive dispersion (Séquaris et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…By strongly associating with the clay surfaces of WDC, transport of OM into deeper soil layers is also possible (Séquaris et al, 2010). Mechanical and chemical processes in soil are key factors which affect the stability of soil aggregates and thus the release and stability of mobile WDCs such as a combination of hydrodynamic parameters (intensive rain, splash erosion, infiltration water rate) and chemical dispersion conditions (the presence of organic matter, increasing pH, decreasing ionic strength and increasing sodium adsorption ratio (SAR)) (Jarvis et al, 1999;Kjaergaard et al, 2004a, b). It has been shown that shaking soil aggregates in low-ionic strength water simulates erosive dispersion (Séquaris et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The boundary soil water pressure was constant with depth and plot (Table 3). In similar simulation studies, Saxena et al (1994), Andreu et al (1994), Jarvis and Larsson (1998), Jarvis et al (1999), Larsson and Jarvis (1999a), Armstrong et al (2000), and Roulier and Jarvis (2003b) used the values of -12, -10, -12, -10, -10, -10, and -10 cm (average with depth) for the boundary soil water pressure in long-term studies conducted on a clayey, clayey, clayey, silty clay over clay, clayey, clayey, and clayey soil, respectively, which are pre�y close to our value (-7 cm).…”
Section: Resultsmentioning
confidence: 76%
“…Since the soil structure or inter-aggregate pores below the 15-cm depth was clearly defined, water might readily flow through the macropores. In long-term simulation of water and solute/pesticide transport through the profiles of clayey, sandy, clayey, silt loam, clayey, silty clay over clay, clayey, and clayey soils, Jarvis et al (1991b), Saxena et al (1994), Andreu et al (1994), Jarvis (1995), Jarvis and Larsson (1998), Jarvis et al (1999), and Armstrong et al (2000) used the values of 0.05, 0.01, 0.1, 0.1, 0.1, 0.1, 0.1, and 0.05 mm/h (average with depth) for the boundary hydraulic conductivity, respectively, which are similar to our values (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations